Diagnóstico ambiental participativo como subsídio à educação ambiental na Aproliso, município de Pato Branco - PR - Klipel, Adelir (2009)
To promote environmental education through a participatory diagnosis in view of environmental improvement, enabling the incorporation of the bases of sustainability economic processes in small farms, encouraging the creative potential of individuals. To this end, we conducted this study at the Association of Rural Producers Line Soares (APROLISO) and to support environmental education in informal small farm. Presenting a brief history of the occupation of the Southwest region of Parana state, justify the existence of the high percentage of properties with smaller areas, where he pursues a subsistence farming, but with capitalist characteristics. With diagnostic actions made possible by visits to properties and group meetings, informal discussions journaled field, we obtained the potentials and the main challenges of life in association listed by the famers themselves. Using the methodology of action research, we conducted a survey of the environmental conditions of small farms, especially the conditions of the springs and the quality of water consumed. Through tests on water samples from different sources in terms of protection, we find that the water is not able to drinkability, because agricultural practices of growing grain and milk production and the inadequacy of rural facilities. also highlight of the concern of this class of workers at the prospect of sustainability of small holdings, the necessity of compliance against the mandatory maintenance of preservation areas and legal reserves. Mentioned the public policy of encouraging and increasing the agricultural activities at the federal, state and district. Even the concern of this research is not with the results, but with the process, we present a possibility of economic viability and management / environmental impact of small farms of the association s procedures and suggestions to be adopted by farmers under the guidance and supervision of specialized technical bodies officers, especially the Departments of Farmer and the Environment of the city.